Required Navigation Performance (RNP) Analysis for ADS-B Data of Makassar-Jakarta Flight using Dot Product Method - N Ruseno; A Putra (Institut Teknologi Bandung, 2021)
Required Navigation Performance (RNP) is known as a performance parameter for a navigation system, where its function is to keep an aircraft within a certain radius of containment. During the flight, an aircraft transmits its real-time location-based on Global Navigation Satellite Systems (GNSS) technology via Automatic Dependence Surveillance Broadcast (ADS-B) protocol. However, there are questions about the flight position accuracy. This research aims to analyze the accuracy of ADS-B flight data about RNP requirements. The flight data used is gathered from the FlightRadar24 website and filtered for each flight phase. The selected route used is Makassar (UPG) – Jakarta (CGK) because the route has the highest number of flights per week. The Dot Product method is proposed to calculate the distance between the flight trajectory to the line of flight procedure towards the destination airport. The analysis is conducted based on the compliance of the flight data to the RNP threshold. It is concluded that the majority of evaluated flights in the selected route fly within the RNP boundary. However, some non-complying flights become within the RNP boundary when they are evaluated with other possible published procedures